Pengaruh Kualitas Produk dan Sikap Merek Terhadap Minat Pembelian Ulang (Survei Pada Pengguna Laptop Acer diForum Kaskus) - Fitria Ashafira Andika Reina, - (2021)
The growth and development of sales of laptop devices in Indonesia is very rapid, marked by the increasing consumer demand for laptop devices. One of them is an Acer Laptop which has a pretty good performance, with an Intel core i5 processor that is tough enough so that it can make users easily run games with high graphics settings, while Acer itself has provided Windows 10 Home 64-bit for free, this means that users no longer need to increase the cost of purchasing and installing a computer operating system. This study aims at product quality, brand attitude, repurchase and the extent to which product quality and brand attitude influence the repurchase interest of Acer laptop users. The method used in this research is descriptive and verification research methods with an explanatory survey method approach. The population in this study were Acer laptop users on the Kaskus forum with a sample size of 82 respondents with the determination of the sample using the Slovin proportional formula. The method of analysis uses descriptive data analysis using the ideal actual score, while the verification data analysis uses path analysis and hypothesis testing. Research results show that the quality of Acer laptop products at the Kaskus forum is categorized as good and good. The brand attitude towards Acer laptop users in the Kaskus forum is considered to be quite good. Repurchase interest in Acer laptop users on the Kaskus forum is good enough. The effect of product quality and brand attitude on repurchase interest in Acer laptop users on the Kaskus forum has a positive and significant effect. The major influence dimension on repurchase interest is conformance which is a dimension of product quality and affective which is a dimension of brand attitude.